2012
DOI: 10.1111/j.1540-8167.2012.02340.x
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Ventricular Tachycardias Using Remote Magnetic Navigation: A Consecutive Case–Control Study

Abstract: The use of MNS offers advantages for ablation of NSHD-VT, while it offers similar efficacy for SHD-VT. (J Cardiovasc Electrophysiol, Vol. 23, pp. 948-954, September 2012).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 28 publications
1
39
1
Order By: Relevance
“…The authors of the review concluded that although the data for remote magnetic navigation for scar-related VT ablation are promising, more comparative and randomized studies are needed to assess superiority [88]. Studies published after this review have further established that remote magnetic navigation have at least similar efficacy compared with manual VT ablation, with a low complication rate [91]. This technique has also demonstrated safety and efficacy in ablating VT storm in ICD-implanted ischemic cardiomyopathy patients [92].…”
Section: Remote Ventricular Arrhythmia Ablationmentioning
confidence: 81%
“…The authors of the review concluded that although the data for remote magnetic navigation for scar-related VT ablation are promising, more comparative and randomized studies are needed to assess superiority [88]. Studies published after this review have further established that remote magnetic navigation have at least similar efficacy compared with manual VT ablation, with a low complication rate [91]. This technique has also demonstrated safety and efficacy in ablating VT storm in ICD-implanted ischemic cardiomyopathy patients [92].…”
Section: Remote Ventricular Arrhythmia Ablationmentioning
confidence: 81%
“…Manipulating a catheter in some positions has also been associated with an increase in the risk of major procedure-related complications, including pericardial effusion or tamponade [10]. Mapping and ablation using a remote magnetic navigation (RMN) may offer advantages during VT procedure compared to manual techniques [11][12][13]. Moreover, especially for severe IHF (SIHF) patients with left ventricular ejection fraction (LVEF) less than 30%, available experience on long-term outcomes of ES treated by acute catheter ablation with RMN is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that catheter ablation using RMN is more effective and safe with idiopathic VA as compared with VA associated with structural heart disease [21][22][23][24]. These reports showed that catheter ablation using RMN was effective and safe with VA originating from the different LV sites including fascicles, papillary muscle, and aortic cusps.…”
Section: Rmn Ablation With Idiopathic Va Originating From the LVmentioning
confidence: 71%